2008
DOI: 10.1080/07357900801918611
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine Combined with Gefitinib in Patients with Inoperable or Metastatic Pancreatic Cancer: A Phase II Study of the Hellenic Cooperative Oncology Group with Biomarker Evaluation

Abstract: The combination of gemcitabine and gefitinib was evaluated in advanced pancreatic cancer. Totally, 53 patients were treated with a 7 week cycle of gemcitabine (1,000 mg/m(2) given weekly) followed by six 4 week cycles of gemcitabine given on days 1, 8 and 15. Gefitinib 250 mg was administered daily. Responses were seen in 6, and stabilization of the disease in 12 patients. The main toxicity was myelotoxicity (92%). The 6-month progression-free survival (PFS) was 30%. Median PFS was 4.1 months and median surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 30 publications
1
40
0
1
Order By: Relevance
“…These tumors, therefore, are ideal for targeted therapeutic strategy since both ErbB1 and ErbB2 receptors along with their downstream proteins have been shown to promote cell growth and survival, and mediate resistance to chemotherapy. Many studies have been published describing the effects of newer molecular agents directed against ErbB1 and ErbB2 receptors in pancreatic neoplasms (8)(9)(10)(11), however, despite theoretical advantages; these agents have failed to yield significantly beneficial results, either alone or in combination with conventional cytotoxic drugs. Although, the exact mechanisms responsible for failure to respond are a matter of intense scrutiny, it seems that a significant number of patients develop drug resistance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These tumors, therefore, are ideal for targeted therapeutic strategy since both ErbB1 and ErbB2 receptors along with their downstream proteins have been shown to promote cell growth and survival, and mediate resistance to chemotherapy. Many studies have been published describing the effects of newer molecular agents directed against ErbB1 and ErbB2 receptors in pancreatic neoplasms (8)(9)(10)(11), however, despite theoretical advantages; these agents have failed to yield significantly beneficial results, either alone or in combination with conventional cytotoxic drugs. Although, the exact mechanisms responsible for failure to respond are a matter of intense scrutiny, it seems that a significant number of patients develop drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Transtuzumab (ErbB2) (11), erlotinib (ErbB1) (10), cetuximab (ErbB1) (8) and gefitinib (ErbB1) (9) have been studied in the last few years; however, none of these drugs has shown any significant improvement in mortality when compared to treatment with conventional cytotoxic drugs. It was observed that most patients eventually developed drug resistance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of rapid resistance to gemcitabine may be due to either stem-like subpopulations of tumor cells, which have innate resistance to chemotherapy, or be caused by molecular changes in cancer cells, such as alternations of transport and metabolism of gemcitabine or the upregulation of phosphatidylinositol 3-kinase (PI3K)/protein kinase B (Akt) or the DNA repair pathway (8)(9)(10)(11)(12). In addition to monotherapy, there are clinical treatments with gemcitabine in combination with other biological or chemotherapeutical targeted agents, such as the epidermal growth factor receptor (EGFR) inhibitors erlotinib, tipifarnib and gefitinib (13,14), but the combinations are limited, with unsatisfactory efficacy. Only patients developing a rapid response upon erlotinib could benefit from EGFR-targeted therapy (13,15).…”
Section: Introductionmentioning
confidence: 99%
“…Combinations of conventional cytotoxic drugs such as gemcitabine, a nucleoside analog that targets cells in S-phase of the cell cycle, with novel agents that target key signaling pathways that control cancer cell survival, proliferation, and/or invasion is a promising approach, and has been attempted in several clinical trials (17)(18)(19)(20)(21). Clinical trials of combinations of TKIs with gemcitabine have been attempted in pancreatic, bladder, NSCLC, ovarian, and other malignancies with little benefit to patients (9,(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%